(3OjhGf GeQF GdbjSs - (3GeQD GdbjS Hf MLQ Hf GdMGQK GdcfOj, ef Hfj Bcd GdeQGQ , J (B80 (3b g`s
(3ChdgG (B:s
(3HYO GdHSedI(B: (3bQCfG Ydi CHj GSGeI CYRg Gddg bGd GeQD GdbjS baGfHc ef PcQi MHjH hefRd HSbW Gddhi Hjf GdONhd aMhed s
(3BNQgG (B:s
(3ef YRjR ade JDef HhGFbg hef JgqVe eCchd heTQhH s
(3Vef eLehY , JQJjHgG (B: (3ef U (B310 - (3U(B338s
(3GdfSNI HgG MhGTs
(3fSNI KGfjIs
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B3 - (3U (B32 ; (3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B776s
Keywords: (3GdCOHs